Wavelengths of LED light affect the growth and cannabidiol content in Cannabis sativa L - Wei, Xiuye; Zhao, Xinlin; Long, Songhua; Xiao, Qingmei; Guo, Yuan; Qiu, Caisheng; Qiu, Huajiao; Wang, Yufu (Industrial crops and products, 2021)
•Ratios of red and blue LED light significantly affect the growth of hemp.•Ratios of red and blue LED light notably affect the CBD content in hemp.•LED light affects CBD yield by changing flower biomass and CBD content. Given the special pharmacological value of cannabidiol (CBD), industrial hemp (hemp) has become a real “hot” crop. Though indoor farming of hemp has been widely used, the effects of red and blue light-emitting diode (LED) acting as supplementary light on the CBD synthesis in hemp remains unclear. Herein, a pot experiment with six treatments [CK, high-pressure sodium as light source, (R:B (ratio of red light to blue light) 9.30:1, PPFD (photosynthetic photon flux density) 191); LED1 (R:B 9.20:1; PPFD 129); LED2 (R:B 1.61:1; PPFD 540); LED3 (R:B 6.47:1; PPFD 28.2); LED4 (R:B 7.15:1; PPFD 41.7); LED5 (R:B 16.8:1; PPFD 252)] was carried out to study the effects of LED light quality on the growth and cannabinoid synthesis of hemp. Results showed that LED2 and LED5 could well maintain hemp growth compared with CK in terms of plant height, stem diameter, and leaf numbers. Compared with CK, the treatment of LED1, LED4, and LED3 significantly decreased the aboveground biomass, while LED2 and LED5 notably improved the aboveground biomass with an increment of 15.2 % and 55.1 %; the biomass of hemp flowers for LED2 and LED5 was markedly increased compared with that for CK with increments of 238 % and 61.5 %, respectively, but the other LED light treatments significantly reduced the flowers yield; LED2 could significantly increase the CBD content of both leaves (1.81 %) and flowers (5.83 %) compared to CK (leaves 1.38 %, flowers 4.27 %) while LED5 only notably increased the CBD content of leaves; among the LED treatments, the theoretic CBD yield for a per plant of LED2 and LED5 was 26.8 % and 9.0 % higher than that of CK. In conclusion, different red and blue LED light intensity ratios would dramatically influence the growth and cannabinoid synthesis of hemp, LED2 and LED5 can be good choices for indoor farming of hemp targeted for higher CBD yield.